A method for constructing cement-modified tailings roadbed
By precisely controlling the moisture content of tailings and the amount of cement used on-site, and combining this with SEM scanning technology to analyze the particle composition of tailings, the construction problem of using tailings as roadbed filler was solved, the strength and stability of the roadbed were improved, and the efficient utilization of tailings was achieved.
Patent Information
- Application Number
- CN202511324598.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-09-17
AI Technical Summary
Existing technologies cannot effectively utilize tailings as roadbed fillers, and cement-modified tailings cannot achieve the same laboratory results on the construction site, resulting in insufficient roadbed strength and stability.
By analyzing the particle composition and water film thickness of the tailings using SEM scanning technology, and combining this with precise control of the on-site moisture content, the cement dosage and water-cement ratio are calculated. On-site mixing and compaction are then employed to ensure that the tailings and cement react fully.
It improved the structural strength and stability of the roadbed, enabled the efficient utilization of tailings, and reduced construction costs and resource waste.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of roadbed construction methods, and particularly relates to a cement-modified tailings roadbed construction method. Background Technology
[0002] Tailings are solid waste discharged by ore beneficiation plants after extracting useful components from the ore. Currently, the main ways to reuse tailings are to produce sintered bricks and steam bricks and to backfill mined-out areas. However, these methods cannot completely eliminate tailings. A large amount of tailings that are not comprehensively utilized are still mainly disposed of by stockpiling. This not only forces companies to build tailings dams and bear high infrastructure costs, but also occupies valuable land resources.
[0003] With the rapid development of highways, the demand for road construction materials is increasing. The shortage of road construction materials has seriously restricted the development of highway construction, especially in plain areas. Due to the restriction of basic farmland, it is very difficult to obtain soil from the surrounding areas. In plain areas, the soil filling height of roads is generally between 3 and 5 meters. The demand for roadbed fill material for expressways exceeds 300,000 tons / km. Tailings have similar geometric shape and chemical composition to natural aggregates and soil, and can be used as substitutes. Using tailings to prepare roadbed fill material can not only provide a better outlet for the large-scale disposal of tailings, but also solve the problem of roadbed fill material supply, which is a win-win approach.
[0004] Tailings themselves lack adhesive components, with a plasticity index less than 5, making it unable to form good cohesion. Cement, as a commonly used solidifying and binding material, is generally used to consolidate materials lacking cohesion, such as silt and gravel. Improving tailings with cement can give them higher strength and stability, thus preparing fillers suitable for roadbed use. Cement-improved tailings typically involve drying the tailings and then determining the optimal moisture content through laboratory compaction tests. Currently, the interaction between tailings and cement, and the control of moisture content, rely entirely on laboratory tests, making it difficult to achieve optimal performance. Furthermore, laboratory tailings require complete drying, and any added water can react with the cement. However, in actual construction sites, tailings cannot be completely dried, and they contain both free and bound water. Free water participates in the cement mixing reaction process. Therefore, if the construction site controls the moisture content according to the optimal laboratory results, the achieved results often differ from the laboratory results.
[0005] Therefore, there is an urgent need for a cement-modified tailings roadbed construction method to solve the above problems. Summary of the Invention
[0006] To overcome the shortcomings of the existing technology, this invention provides a cement-modified tailings roadbed construction method. This invention uses cement for modification, and by combining the characteristics of tailings raw materials and precisely controlling the on-site moisture content, it ensures sufficient interaction between tailings, water, and cement, thereby improving the overall structural strength and stability of the roadbed.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A method for constructing cement-modified tailings roadbed, the specific steps of which are as follows:
[0009] S1. Determine the moisture content and particle composition of the tailings;
[0010] S2. Obtain the chord length and arc length of tailings particles using SEM scanning technology, and calculate the average particle size of tailings within each particle size range.
[0011] S3. Calculate the thickness of the water film on the surface of the tailings after centrifugation based on the specific surface area of the tailings and the mass of water adsorbed on the surface of the tailings after centrifugation.
[0012] S4. Based on experience, determine the amount of cement and the water-cement ratio in cement-modified tailings subgrade materials, and determine the moisture content control value of cement-modified tailings subgrade materials during construction.
[0013] S5. Distribute the tailings evenly on the roadbed, ensuring that the moisture content reaches the control value of ±1%. Then, spread cement evenly and mix it with the tailings on-site. Level the mixture with a grader and finally compact it with a heavy roller.
[0014] Preferably, in step S1, the moisture content of the dried tailings is determined, and the particle composition of the tailings is determined by screening test.
[0015] Preferably, in step S2, the method for obtaining the chord length and arc length of the tailings particles is as follows: take 10-15g of dried tailings samples within each particle size range, place them on the workbench, and use SEM scanning technology to collect images of the tailings distribution within each particle size range on the workbench. Filter and histogram equalization are performed on the images, and then the chord length and arc length of the tailings particles in the images are extracted.
[0016] Preferably, in step S2, the formula for calculating the average particle size of tailings within each particle size range is:
[0017] ;
[0018] ;
[0019] ;
[0020] ;
[0021] In the formula:
[0022] r a - Tailings particle size in the image with a central angle θ of 2π, in mm;
[0023] s a - The arc length of the tailings particles in the image with a central angle θ of 2π, in mm;
[0024] c b - The chord length of tailings particles in the image where the central angle θ is 0 < θ ≤ π, in mm;
[0025] r b - Tailings particle size in the image where the central angle θ is 0 < θ ≤ π, in mm;
[0026] s b - The arc length of tailings particles in the image where the central angle θ is 0 < θ ≤ π, in mm;
[0027] c c - The chord length of tailings particles in the image where the central angle θ is π < θ < 2π, in mm;
[0028] r c - The central angle θ in the image represents the tailings particle size, in mm, where π < θ < 2π.
[0029] s c -The arc length of the tailings particles in the image with a central angle θ of π < θ < 2π, in mm;
[0030] r k - The average particle size of tailings within the k-th particle size range, in mm;
[0031] n - The number of tailings in the image with a central angle θ of 2π;
[0032] i - The number of tailings in the image whose central angle θ is 0 < θ ≤ π;
[0033] The number of tailings in the j-image where the central angle θ is π < θ < 2π.
[0034] Preferably, in step S3, 50-100g of naturally undried tailings with a particle size of 0.6mm-1.18mm is taken, and the tailings are placed in a sealed container and centrifuged for 2-3 minutes with absorbent paper placed at the bottom of the container; the mass of the tailings after centrifugation is then weighed, the tailings are dried, and the mass of the dried tailings is weighed to obtain the specific surface area of the tailings and the mass of water adsorbed on the surface of the tailings after centrifugation.
[0035] Preferably, the formula for calculating the thickness of the water film on the surface of the tailings after centrifugation is:
[0036] ;
[0037] ;
[0038] In the formula:
[0039] SA 0.6~1.18 - Specific surface area of tailings with a particle size of 0.6mm to 1.18mm, in m² 2 / kg;
[0040] r w - Density of tailings, g / cm³ 3 ;
[0041] r 0.6~1.18 - Average particle size of tailings with a particle size of 0.6mm to 1.18mm, in mm;
[0042] μ - the thickness of the water film on the surface of the tailings after centrifugation, in μm;
[0043] m l - The mass of tailings with a particle size of 0.6mm to 1.18mm after centrifugation, in grams;
[0044] m h - The mass of dried tailings with a particle size of 0.6mm to 1.18mm, in g;
[0045] r s - Density of water, g / cm³ 3 .
[0046] Preferably, the formula for calculating the moisture content control value is:
[0047] ;
[0048] In the formula:
[0049] w-Moisture content control value in cement-improved tailings subgrade construction, %
[0050] P s - Cement usage in cement-improved tailings roadbed materials, %
[0051] - The water-cement ratio of cement-modified tailings roadbed materials;
[0052] μ - the thickness of the water film on the surface of the tailings after centrifugation, in μm;
[0053] k - The number of tailings to be categorized by particle size;
[0054] P k - The percentage of the k-th particle size in the tailings, %
[0055] r w- Density of tailings, g / cm³ 3 ;
[0056] r k - The average particle size of tailings within the k-th particle size range, in mm;
[0057] r s - Density of water, g / cm³ 3 .
[0058] Preferably, the cement content in the cement-improved tailings roadbed material is 3.0-4.0%; the water-cement ratio is 0.45-0.55.
[0059] Preferably, the tailings have a particle size ≤1.18mm; the content of tailings with a particle size less than 0.075mm is ≤70%; and the moisture content of tailings under natural conditions is ≤14%.
[0060] Preferably, in step S5, after the tailings are evenly distributed on the roadbed, their moisture content is measured. If the moisture content is higher than the moisture content control value ±1%, the tailings are dried; if the moisture content is lower than the moisture content control value ±1%, water is sprayed. The filler for cement-modified tailings roadbed is laid in layers with a thickness of 30-40cm, and the minimum compacted thickness of the last layer to the top of the roadbed is ≥10cm.
[0061] The advantages of this invention are:
[0062] (1) This invention uses cement to improve tailings. Combining the characteristics of tailings raw materials, the invention uses precise control of the moisture content on site to enable the tailings, water and cement to fully interact, thereby improving the overall structural strength and stability of the roadbed. The invention is used to scientifically calculate the moisture content control value during the construction process, so that the interaction between cement and tailings can play the best role, thereby ensuring good construction quality.
[0063] (2) This invention addresses the defects in the on-site construction of cement-modified tailings. Based on the characteristics of tailings materials, it fully considers the interaction between tailings, water, and cement during construction. It combines the thickness of the water film on the surface of tailings to ensure that free water and cement react fully. When the raw materials of tailings and the amount of cement used change, the on-site construction moisture content control value is calculated in real time, thereby ensuring that the performance of cement-modified tailings roadbed materials reaches the optimal level and improving the quality of the project.
[0064] (3) This invention uses microscopic image recognition technology to analyze the composition of tailings particles and calculates the average particle size of tailings in each particle size range. Based on this, and combined with relevant experimental methods, the thickness of the water film on the surface of the tailings after centrifugation and the mass of adsorbed water on the surface of the tailings are accurately calculated. The interaction between free water and cement is also considered to obtain the on-site construction moisture content control value. This method takes into account the influence of tailings with different particle sizes, which greatly improves the accuracy of the results and provides a scientific and accurate calculation method for the on-site construction moisture content control value of cement-modified tailings.
[0065] (4) Based on relevant parameters such as raw materials and cement usage of tailings on site, this invention calculates the control value of moisture content of cement-improved tailings for on-site construction, which greatly reduces the amount of testing and improves work efficiency; and the use of industrial waste tailings in roadbed fill material realizes waste utilization and saves resources. Detailed Implementation
[0066] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0067] Example 1
[0068] S1. The copper tailings were dried and their moisture content was determined to be 13.8%. The particle composition of the copper tailings was determined by sieve analysis. The density of water was taken as 1 g / cm³. 3 Density of dried copper tailings r w It is 2.81 g / cm 3 The dried copper tailings were screened, and the results are shown in Table 1 below:
[0069] Table 1 Screening results of copper tailings
[0070] ;
[0071] S2. Take 11g of dried copper tailings samples from each particle size range and place them on the workbench. Use SEM scanning technology to acquire images of the copper tailings distribution within each particle size range on the workbench. Filter and histogram equalization are performed on the images to extract the chord length and arc length of the copper tailings particles in the images. The results are shown in Table 2 below:
[0072] Table 2. Parameter values extracted from copper tailings images within each particle size range.
[0073] ;
[0074] S3. Calculate the average particle size of copper tailings within each particle size range using the following formula. The results are shown in Table 3 below:
[0075] ;
[0076] ;
[0077] ;
[0078] ;
[0079] Table 3 Average particle size of copper tailings within each grade range
[0080] ;
[0081] S4. Take 65g of naturally undried copper tailings with a particle size of 0.6mm~1.18mm. Place the copper tailings in a sealed container and centrifuge for 2 minutes, placing absorbent paper at the bottom of the container. Weigh 61.1g of the centrifuged copper tailings. Dry the copper tailings and weigh 55.5g of the dried tailings. Calculate the water film thickness on the surface of the copper tailings after centrifugation based on the specific surface area of the copper tailings and the mass of water adsorbed on the surface of the copper tailings after centrifugation. The calculation formula is as follows:
[0082] = 2.26m 2 / kg;
[0083] = 4.5um;
[0084] S5. Based on relevant engineering experience, the cement content in cement-improved tailings roadbed materials is determined to be 3.5% and the water-cement ratio to be 0.50.
[0085] S6. Based on the cement dosage and water-cement ratio, the moisture content control value of cement-modified tailings subgrade material during construction is calculated to be 12.1% according to the following formula;
[0086] ;
[0087] S7. The copper tailings are evenly distributed on the roadbed, with a layer thickness of 35cm and a loose paving coefficient of 1.2. The loose paving thickness of the copper tailings is determined to be 42cm. The moisture content is measured to be 13.8%, which is 1.7% higher than the moisture content control value of 12.1%. The copper tailings are dried to bring the moisture content to the moisture content control value of 12.1±1%. Then, 3.5% cement is evenly spread and mixed on-site using a BMW mixer. The mixture is leveled using a grader and finally compacted using a heavy roller.
[0088] The copper tailings were dried, and a compaction test was conducted on the 3.5% cement-modified copper tailings according to the method specified in the geotechnical test procedure to determine its optimum moisture content and CBR value.
[0089] Samples of the cement-modified copper tailings mixed on-site were taken, and compaction and CBR tests were conducted to verify the cement dosage, moisture content, and CBR performance of the cement-modified copper tailings. The results are shown in Table 4 below.
[0090] Table 4
[0091] ;
[0092] As shown in Table 4, the CBR value of the field sampling test is higher than that of the indoor test, indicating that the roadbed implemented by the present invention has better stability and higher strength.
[0093] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for constructing cement-modified tailings roadbed, characterized in that, The specific steps are as follows: S1. Determine the moisture content and particle composition of the tailings; S2. Obtain the chord length and arc length of tailings particles using SEM scanning technology, and calculate the average particle size of tailings within each particle size range. S3. Calculate the thickness of the water film on the surface of the tailings after centrifugation based on the specific surface area of the tailings and the mass of water adsorbed on the surface of the tailings after centrifugation. S4. Based on experience, determine the amount of cement and the water-cement ratio in cement-modified tailings subgrade materials, and determine the moisture content control value of cement-modified tailings subgrade materials during construction. S5. Spread the tailings evenly on the roadbed, so that the moisture content reaches the control value of ±1%, then spread cement evenly and mix the cement with the tailings. Level the roadbed with a grader and finally compact it with a heavy roller. In step S1, the moisture content of the dried tailings is determined, and the particle composition of the tailings is determined by sieving test. In step S2, the method for obtaining the chord length and arc length of the tailings particles is as follows: Take 10-15g of dried tailings samples within each particle size range, place them on the workbench, and use SEM scanning technology to collect images of the tailings distribution within each particle size range on the workbench. Filter and histogram equalization are performed on the images, and then the chord length and arc length of the tailings particles in the images are extracted. In step S2, the formula for calculating the average particle size of tailings within each particle size range is: ; ; ; ; In the formula: r a - Tailings particle size in the image with a central angle θ of 2π, in mm; s a - The arc length of the tailings particles in the image with a central angle θ of 2π, in mm; c b - The chord length of tailings particles in the image where the central angle θ is 0 < θ ≤ π, in mm; r b - Tailings particle size in the image where the central angle θ is 0 < θ ≤ π, in mm; s b - The arc length of tailings particles in the image where the central angle θ is 0 < θ ≤ π, in mm; c c - The chord length of tailings particles in the image where the central angle θ is π < θ < 2π, in mm; r c - The central angle θ in the image represents the tailings particle size, in mm, where π < θ < 2π. s c -The arc length of the tailings particles in the image with a central angle θ of π < θ < 2π, in mm; r k - The average particle size of tailings within the k-th particle size range, in mm; n - The number of tailings in the image with a central angle θ of 2π; i - The number of tailings in the image whose central angle θ is 0 < θ ≤ π; The number of tailings in the j-image where the central angle θ is π < θ < 2π; The formula for calculating the moisture content control value is: ; In the formula: w-Moisture content control value in cement-improved tailings subgrade construction, % P s - Cement usage in cement-improved tailings roadbed materials, % - Water-cement ratio of cement-modified tailings roadbed material, g; μ - the thickness of the water film on the surface of the tailings after centrifugation, in μm; k - The number of tailings to be categorized by particle size; P k - The percentage of the k-th particle size in the tailings, % ρ w - Density of tailings, g / cm³ 3 ; r k - The average particle size of tailings within the k-th particle size range, in mm; ρ s - Density of water, g / cm³ 3 .
2. The method for constructing cement-modified tailings roadbed according to claim 1, characterized in that: In step S3, take 50-100g of naturally undried tailings with a particle size of 0.6mm-1.18mm, place the tailings in a sealed container and centrifuge for 2-3 minutes, with absorbent paper placed at the bottom of the container; weigh the tailings after centrifugation, dry the tailings, and weigh the dried tailings to obtain the specific surface area of the tailings and the mass of water adsorbed on the surface of the tailings after centrifugation.
3. A method for constructing cement-modified tailings roadbed according to claim 1 or 2, characterized in that, The formula for calculating the thickness of the water film on the surface of the tailings after centrifugation is: ; ; In the formula: SA 0.6~1.18 - Specific surface area of tailings with a particle size of 0.6mm to 1.18mm, in m² 2 / kg; ρ w - Density of tailings, g / cm³ 3 ; r 0.6~1.18 - Average particle size of tailings with a particle size of 0.6mm to 1.18mm, in mm; μ - the thickness of the water film on the surface of the tailings after centrifugation, in μm; m l - The mass of tailings with a particle size of 0.6mm to 1.18mm after centrifugation, in grams; m h - The mass of dried tailings with a particle size of 0.6mm to 1.18mm, in g; ρ s - Density of water, g / cm³ 3 .
4. The method for constructing cement-modified tailings roadbed according to claim 1, characterized in that: The cement content in the cement-improved tailings roadbed material is 3.0-4.0%; the water-cement ratio is 0.45-0.
55.
5. The method for constructing cement-modified tailings roadbed according to claim 1, characterized in that: The tailings have a particle size ≤ 1.18 mm; the content of tailings with a particle size less than 0.075 mm is ≤ 70%; and the moisture content of the tailings under natural conditions is ≤ 14%.
6. The method for constructing cement-modified tailings roadbed according to claim 1, characterized in that: In step S5, after the tailings are evenly distributed on the roadbed, their moisture content is measured. If the moisture content is higher than the moisture content control value ±1%, the tailings are dried. If the moisture content is lower than the moisture content control value ±1%, water is sprayed. The filler for cement-modified tailings roadbed is spread in layers with a thickness of 30-40cm, and the minimum compaction thickness of the last layer to the top of the roadbed is ≥10cm.
Citation Information
Patent Citations
Method for evaluating construction uniformity of clay improved copper tailing roadbed
CN120195383A
Production method of copper-doped tailing pavement base material
CN120383456A